The Effect of Age on the Relationships between Work‐related Factors and Heavy Drinking. Issue 2 (3rd October 2014) - Morikawa, Yuko; Nakamura, Koshi; Sakurai, Masaru; Nagasawa, Shin‐Ya; Ishizaki, Masao; Nakashima, Motoko; Kido, Teruhiko; Naruse, Yuchi; Nakagawa, Hideaki
Abstract : The Effect of Age on the Relationships between Work‐related Factors and Heavy Drinking: Yuko MORIKAWA, et al . Department of Epidemiology and Public Health, Kanazawa Medical University —Aims: The aim of this study was to investigate age‐related differences in the relationship between Work‐related factors and heavy drinking. Methods: This study in 3, 398 male workers at a factory in Japan examined data on heavy drinking, defined as an alcohol consumption >40 g/day, and work‐related factors including occupation, shift work, and job stress evaluated using the Japanese version of the Karasek's Job Content Questionnaire (JCQ). In the present cross‐sectional study, alcohol consumption was assessed using a self‐administered diet history questionnaire (DHQ). Results: The prevalence of heavy drinkers in the study population was 15.5% and rose with increasing age. An increase in the odds ratio (OR) for heavy drinking was observed consistently in blue‐collar workers compared with white‐collar workers in all age groups. In subjects aged 20−29 years, shift work had also increased the OR for heavy drinking. In subjects aged 40−49 years, the two groups with a lower decision latitude had an increased OR compared with the highest group. In subjects aged 20−29 years, the age adjusted OR for individuals who Received the lowest level of social support in the workplace was increased significantly compared with the highest group (4.22 [95%CI, 1.07−16.62]). On the other hand, social support showed a positive association with heavy drinking in subjects aged 40−49 and 50−59 years. Job demand was not related to heavy drinking in any of the age groups. Conclusions: Our findings suggest that occupation and work schedule are related to alcohol use more apparently in a younger age group and that psychosocial factors are related to enhancement or prevention of alcohol use.